Management of late adverse effects after chemoradiation for anal cancer. (2nd December 2021) - Haas, Susanne; Mikkelsen, Anette H.; Kronborg, Camilla; Oggesen, Birthe T.; Faaborg, Pia Moeller; Serup-Hansen, Eva; Spindler, Karen-Lise G.; Christensen, Peter
Abstract: Background and purpose: Significant improvements in the treatment of anal cancer have produced a growing population of anal cancer survivors. These patients often experience late adverse effects related to their treatment. Research has revealed substantial unmet needs because of long-term symptoms and functional impairments after treatment that may negatively affect health-related quality of life. The purpose of the present guidelines is to review the scientific evidence for the management of late adverse effects after (chemo)radiotherapy ([C]RT) for anal cancer and to extrapolate knowledge from other pelvic malignancies treated with pelvic (C)RT so that they may guide the clinical management of late adverse effects. Materials and methods: Relevant studies were systematically searched in four databases from their inception to June 2020 (no language limitation) and guidelines were searched in 16 databases, focussing on bowel dysfunction, psychosocial aspects, pain, and sexual and urinary dysfunction. The guidelines were developed by a panel of experts using the Oxford Centre for Evidence-based Medicine, levels of evidence, and grades of recommendations. Scientific evidence: Late adverse effects after (C)RT for anal cancer are associated with a low overall quality of life among survivors. The most pronounced late adverse effects are bowel dysfunction (present in up to 78%), urinary dysfunction (present in up to 45%), and sexual dysfunction (present in up to 90% of men and up to 100% of women). Only indirect data on adequate treatment options of these late adverse effects for anal cancer are available. Conclusion: Quality of life and late adverse effects should be monitored systematically following treatment for anal cancer to identify patients who require further specialist evaluation or support. Increased awareness of the extent of the problem may serve to stimulate and facilitate multidisciplinary collaboration, which is often required.